If you need to love someone - JRM; Sony Music Entertainment (M). (Ampang, Selangor : Sony Music Entertainment, 1999)
Contains the single taken from JRM's debut album.
CD 1 : If You Need To Love Someone.
Koleksi Khas Wiramanja.
Group members: Terence, Wilson, Kelvin, Mozad, Jason, Timothy.
Title from disc label.
Keywords: Songs, English